Developing an Ethical Scale to Measure Instagram Use Motivation Among College Students: Investigating Demographic Factors - Fereshteh Lotfi; Farid Ahmadi; Mahsa Esmailirad (International Journal of Management, Accounting and Economics)
This study aimed to measure Instagram use motivations and explore potential differences based on gender, age, marital status, and academic background among Iranian college students. A scale was developed with 6 dimensions and 27 items, and its reliability and validity were confirmed. Statistical methods including t-tests, one-way analysis, and Friedman test were used to analyze the data. Results showed high reliability and significant differences in motivation levels and dimensions across demographic groups. Females exhibited higher motivation levels than males, and individuals above 30 years showed higher motivation. Married individuals demonstrated higher motivation levels than singles. The most prevalent motivation for using Instagram was passing time, while self-expression was the least common motivation. The scale was deemed suitable for measuring motivation levels for using Instagram among Iranian college students. The study's findings highlighted distinct patterns of motivation based on gender, age, marital status, and academic background, providing valuable insights into Instagram use. By identifying and analyzing significant motivational differences across diverse demographic factors, this study not only enriches the understanding of social media usage in a unique cultural setting but also provides a foundation for future research on social media behavior in similar contexts.